2005
DOI: 10.1002/cne.20664
|View full text |Cite
|
Sign up to set email alerts
|

Species differences in tachykinin receptor distribution: Further evidence that the substance P (NK1) receptor predominates in human brain

Abstract: Marked species differences in the distribution of central tachykinin receptors are reported but uncertainty remains about the ability of available ligands to detect NK2 and NK3 receptors in human brain. We compared the distribution of NK1, NK2, and NK3 receptors in sections from rodent, primate, and human brain using the 125I-labeled ligands substance P (SP) for the NK1 receptor, neurokinin A (NKA) for the NK2 receptor, and neurokinin B (NKB) and eledoisin for NK3 receptors. Duration of exposure to autoradiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 67 publications
2
48
1
Order By: Relevance
“…However, no NK 3 receptors have been detected, to date, within the mesencephalic dopaminergic neurons (Dietl and Palacios, 1991;Whitty et al, 1994Whitty et al, , 1997. Thus, in addition to the complications of using preclinical species to evaluate the functional role of the NK 3 receptors, there is also some controversy with regard to the specific localization and density of NK 3 receptors within the human brain (Rigby et al, 2005). Although, in this regard our in house studies, using autoradiographic and immunohistochemical techniques, have detected widespread but low-level expression of the NK 3 receptors within human brain (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no NK 3 receptors have been detected, to date, within the mesencephalic dopaminergic neurons (Dietl and Palacios, 1991;Whitty et al, 1994Whitty et al, , 1997. Thus, in addition to the complications of using preclinical species to evaluate the functional role of the NK 3 receptors, there is also some controversy with regard to the specific localization and density of NK 3 receptors within the human brain (Rigby et al, 2005). Although, in this regard our in house studies, using autoradiographic and immunohistochemical techniques, have detected widespread but low-level expression of the NK 3 receptors within human brain (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…In the mammalian brain, NK 3 receptors are expressed within medial prefrontal cortex (mPFC), thalamus, and amygdala, while their presence in midbrain dopaminergic nuclei (the ventral tegmental area (VTA) and substantia nigra (SN)), locus coeruleus, and septal and basal nuclei suggest a role in modulating central monoaminergic systems (Langlois et al, 2001). However, there are considerable species differences in NK 3 receptor expression within the brain (Langlois et al, 2001;Rigby et al, 2005) which can complicate preclinical investigations of this receptor.…”
Section: Introductionmentioning
confidence: 99%
“…The NK3 receptor in the brain typically is found in cortical regions, nuclei of amygdala, hippocampus as well as midbrain structures e.g. substantia nigra, ventral tegmental area and raphe nuclei [208]- [210]. However, it is present in the cerebral regions in low density in comparison with NK1 and NK2 receptors [211].…”
Section: Mammalian Neurokinins and Their Receptorsmentioning
confidence: 99%
“…Three types of G-protein-coupled receptors, denoted NK 1 , NK 2 , and NK 3 , mediate a wide range of biological activities of tachykinins. Neuroanatomical studies have demonstrated that the NK 1 receptor is predominant in the human brain, whereas the expression of NK 2 or NK 3 receptors is either weak or absent (3). NK 1 receptors are widely expressed throughout the central nervous system (3) and are involved in the regulation of various behavioral, endocrine, and autonomic functions.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroanatomical studies have demonstrated that the NK 1 receptor is predominant in the human brain, whereas the expression of NK 2 or NK 3 receptors is either weak or absent (3). NK 1 receptors are widely expressed throughout the central nervous system (3) and are involved in the regulation of various behavioral, endocrine, and autonomic functions. Based on the pharmacological data and recent clinical trials, it has emerged that blockade of brain tachykinin NK 1 receptors may provide a novel treatment of emesis (4,5), major depression (6), and anxiety problems (7).…”
Section: Introductionmentioning
confidence: 99%